2012
DOI: 10.1021/np300446c
|View full text |Cite
|
Sign up to set email alerts
|

Melittin Suppresses VEGF-A-Induced Tumor Growth by Blocking VEGFR-2 and the COX-2-Mediated MAPK Signaling Pathway

Abstract: Melittin (1) is a major polypeptide in honey bee venom that has been used traditionally against chronic inflammation and cancer. However, its molecular mechanism has not been determined. In this study, the antitumor effect of 1 was compared with that of NS398, a cyclooxygenase-2 (COX-2) inhibitor, in vivo and in vitro. Subcutaneous injection of 1 at 0.5 and 5 mg/kg suppressed significantly vascular endothelial growth factor (VEGF)-A-transfected highly metastatic Lewis lung cancer (VEGF-A-hm LLC) tumor growth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 40 publications
1
44
0
1
Order By: Relevance
“…MEL also decreased the expression of VEGF receptor-2, COX-2, and prostaglandin E2 in VEGF-A-transfected HUVECs. These effects were accompanied by a reduction of the phosphorylation of extracellular signal-regulated kinase 1/2 and c-jun N-terminal kinase, whereas it increased the phosphorylation of p38 MAPK [68]. …”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 99%
“…MEL also decreased the expression of VEGF receptor-2, COX-2, and prostaglandin E2 in VEGF-A-transfected HUVECs. These effects were accompanied by a reduction of the phosphorylation of extracellular signal-regulated kinase 1/2 and c-jun N-terminal kinase, whereas it increased the phosphorylation of p38 MAPK [68]. …”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 99%
“…As a typical PFT, melittin can destabilize and create pores inside the cell membranes. By this direct lytic action to the membranes and via additional mechanisms involved in apoptosis, cell cycle arrest or necrosis, melittin can kill tumor cells and significantly inhibit tumor growth (7, 8). These anti-tumor effects are, however, available only with high (above micro-molar) concentration of melittin.…”
Section: Introductionmentioning
confidence: 99%
“…Classical members of MAPK signalling include stress activated protein-kinase 2 (p38), c-Jun N-terminus kinase (JNK) and extracellular signal-regulated kinase (ERK1/2), which play crucial roles in the migration of various cells under VEGF stimulation (Huh et al 2012, Jeong et al 2014. The present study demonstrated that VEGFA enhanced the phosphorylation of p38 protein in hDPSCs.…”
Section: Discussionmentioning
confidence: 51%